IMF History Volume 2 (1945-1965) : Twenty Years of International Monetary Cooperation Volume II; Analysis. (International Monetary Fund, 1996)
This paper discusses the history of the first 20 years of the IMF. It attempts to recount objectively what were its origins and what have been its plans and activities. The paper contains a chronological account of the evolution of the IMF from the original plans formulated in 1941 to the end of 1965, with a supplementary chapter summarizing subsequent events. It analyzes the IMF's policies in three major fields and reviews its constitutional development.